PENGGUNAAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER NHT UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS SISWA PADA MATERI TEKS ANALYTICAL EXPOSITION KELAS XI IPS 2 SMA NEGERI 14 PEKANBARU TAHUN PELAJARAN 2015-2016 - Arnis, Artati (Perspektif Pendidikan dan Keguruan, 2020)
This research was expected to provide benefits for: (1) For learners easier to understand and master English materials with Numbered Heads Together (NHT). (2) The results of this study are expected to provide input to teachers the importance of used NHT Learning Model to improve English learning outcomes. (3) The results of this study were expected to find out the learners' learning outcomes of English subjects delivered used NHT. This research took place in XI IPS 2 class SMAN 14 Pekanbaru Jl. Tengku Bey/Sei. Mintan I. The instrument of this study consists of observation sheet and tests. This study was a classroom action research consisting of four stages namely, planning, action, observation, and reflection. From the results of the study that the initial data was known that the students complete only 15 students with percentage of 42.86% while the student was not complete as many as 20 students with percentage of 57.14%. With an average student score of 74.49. On the completeness of student scores on the first cycle students expressed complete only as many as 24 students with percentage 85.71%. While the students who do not complete as many as 11 students with a percentage of 31.43% with an average student score of 81.94. In this case from the number of students mastery expectations have not been achieved from the number of students as much as 70% of the number of students. On the completeness of student scores on the second cycle of students who expressed thoroughly only as many as 35 students with 100% percentage. While there are no students who were not complete with an average student score of 89.91. In this case from the number of students' mastery expectation had been achieved from 70% of the total number of students as 35 students expressed thoroughly so that in this case there was no need to take action back in the following cycle or research conducted only two cycles